Extraction of Electrical Power Transformer Parameters (International Journal of Engineering and Computer Science, 2013)
In this paper the VISUAL BASIC language is used to design an interactive program that helps in understanding of transformers theory, as well as demonstrating its internal construction, getting its operating characteristics and the equivalent circuit elements. The program helps in minimizing the computational time especially in case of complicated hand calculation and facilitates an easy way for explaining extracting the transformer parameters.